Participatory Evaluation of Open Pollinated Maize (Zea mays L.) Varieties for Green Cob Production Under Irrigation in the North Shewa Lowlands, Ethiopia - Shumet Chakle; Fekadu Tewolde; Dejene Mamo (Advances in Agriculture)
In the experimental area, there is a lack of improved maize varieties for green cob production. The experiment was conducted at Efratana gidim woreda Yimlo Kebele FTC-station in the North Shewa zone during the 2017 and 2018 experimental years under irrigation conditions. The objective of the study was to select adaptive, high-green cob yielders and farmers who preferred open-pollinated maize varieties for the lowland areas of North Shewa. The experiment was laid out in a randomized complete block design with three replications. Six nationally released open-pollinated maize, varieties including local check, were evaluated for two subsequent years. The combined analysis of variance showed highly significant (p<0.01) differences for days to anthesis, days to silking, and number of cobs ha−1. In each year, farmers participated and selected the top preferred varieties. During the 2017 experimental year, farmers used a number of cobs per plant, bear tip, cob length, uniformity, husk tip coverage, earliness, and stalk strength as selection criteria, and during the 2018 experimental year, farmers also used cob length, bear tip, earliness, lodging tolerance, and biomass as variety selection criteria. Varieties Melkasa-2 and Melkasa-6Q have been selected in both years. Analysis of variance revealed that both farmers preferred varieties that gave a high number of cobs, which is 46,914 and 41,358 cobs ha−1 for varieties Melkasa-2 and Melkasa-6Q, respectively. Based on this result, varieties Melkasa-2 and Melkasa-6Q were recommended for the North Shewa lowlands and similar agroecology.